Atypical presentation of lipomatous hypertrophy of the interatrial septum: a case report. Issue 4 (11th November 2019) - Gopal, Dipika J; Han, Yuchi; Silvestry, Frank E; Ferrari, Victor A
Abstract: Background: Lipomatous hypertrophy of the interatrial septum (LHIAS) is a common finding on transthoracic echocardiogram (TTE). Occasionally, the appearance of LHIAS is atypical and multimodality imaging is helpful to make the diagnosis. We present a case of atypical LHIAS to highlight the potential aetiologies for an interatrial septal mass and review features on multimodality imaging that help decrease uncertainty and establish a diagnosis. Case summary: A 64-year-old man with a history of hypertension, diabetes mellitus, and coronary artery disease with multiple percutaneous coronary interventions presented to the emergency room with chest pain. Transthoracic echocardiogram showed a homogenous echo-dense, intracardiac mass present within the interatrial septum. Computed tomography (CT) angiogram of the chest showed a homogenous mass similar in radiodensity to extracardiac and pericardial fat. Cardiac magnetic resonance (CMR) confirmed LHIAS by homogenous signal that was nulled on fat suppression images. Discussion: This case highlights that while most LHIAS has the standard 'dumbbell' appearance on TTE, there are instances where it can appear more like an adherent mass prompting a wider differential. Unenhanced CT of the heart can be used to confirm LHIAS by the presence of low attenuation values for tissue. Alternatively, CMR can be used for tissue characterization and confirmation of LHIAS. Precontrast T2/T1-weighted CMR images with steady-state free precession show high signal intensity in the area of LHIAS and produce a black/hypointense boundary effect between fat and myocardium. A multimodality approach is crucial in arriving at the appropriate diagnosis using the tissue characterization capabilities of CT and CMR.